Pengaruh Stres Kerja Dan Motivasi Kerja Terhadap Produktivitas Kerja : (Survei Pada Driver Maxim Di Kota Tasikmalaya) - Irfan Muhammad Anwar (CV. ULIL ALBAB CORP, 2022)
This research was conducted with the aim to determine the effect of work stress and work motivation on the work productivity of Maxim Driver in Tasikmalaya City. The method used in this study is a survey method using data obtained directly through questionnaires distributed to 100 respondents who are Maxim Drivers in Tasikmalaya City. The technique used in this research is path analysis. Based on the results of the study, it can be seen that work stress has a significant effect on Maxim Driver's Work Motivation in Tasikmalaya City. Job stress has a significant direct effect on work productivity. Motivation has a significant direct effect on Work Productivity. Motivation is able to mediate the effect of work stress on the work productivity of maxim drivers in Tasikmalaya City.